REALISASI ANTENA MIKROSRIP SISTEM AERIAL VIDEO PADA SISI GROUND SEGMENT DI FREKUENSI 5.8 GHZ - Nurbani Nurbani; Yuyun Siti Rohmah; Dwi Andi Nurmantris (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
The shooting method using UAV (Unmaned Aerial Vehicle ) rides is being thoroughly studied and used in the telecommunication world because it has various benefits. The benefits of UAV are aerial shooting and monitoring process at a location. Monitoring using UAV system require a long distance to get maximum results. The problem is transceiver of antennas did not work optimally for long distances. In this study, the micro strip antenna is designed on the ground segment side using T-junction technique. T-junction is a power divider technique that can support impedance matching on transmission line especially for micro strip array antenna. The coupled technique that used in this paper is the proximity portion coupled with the same height of the upper and lower layers. Then, the materials using Epoxy FR-4 substrate with a dielectric constant 4.4 at a frequency of 5.8 GHz. The simulation and measurements resulted the microstrip antenna that has an unidirectional pattern, circular polarization center frequency at 5.8 GHz, with VSWR â‰¤ 2, the impedance value is 50 Î©, the gain is 8.459 dB, where is in accordance with the specifications of the desired antenna.